Edukasi Baby Led Weaning Sebagai Upaya Perbaikan Status Gizi Bayi Dan Balita Di Puskesmas Pattingalloang - Nahira Nahira; Sumarni Sumarni (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Malnutrition is a condition of lack of nutrition for a certain period of time so that the body will break down food reserves under the fat layer and organ layers. MPASI methods are divided into two, namely conventional MPASI, which is fed with a spoon, and the Baby Led Weaning (BLW) method, where the child eats with his own hands. The aim of this community service is that it is hoped that parents can increase their knowledge regarding Baby LED Weaning as an effort to improve the nutritional status of toddlers at the Pattingaloang Community Health Center. This research method uses an experimental design with a one group pretest-posttest approach. The study population was mothers who had toddlers aged at least 6-12 months. Sample collection used purposive sampling technique. results of intervention group research with a sample size of 20 children. The results of the study showed that the difference in the average knowledge score of the pretest and posttest groups was 16.5 with a p value = 0.0001 < α where it was concluded that there was an influence of LED Weaning education as an effort to improve the nutritional status of infants and toddlers at the Pattingaloang Community Health Center.